THE DETERMINANTS OF PROFITABILITY IN COMPANIES LISTED ON THE BUCHAREST STOCK EXCHANGE - SORANA VĂTAVU (Annals of the University of Petrosani: Economics)
This research aims to establish the determinants of financial performance in 126 Romanian companies listed on the Bucharest Stock Exchange, over a period of ten-years (2003-2012). The analysis is based on cross sectional regressions. Return on assets is the performance proxy, while the variables expected to have a significant impact on profitability are debt, asset tangibility, size, liquidity, taxation, risk, inflation and crisis. Regression results indicate that profitable companies operate with limited borrowings. Tangibility, business risk and the level of taxation have a negative impact on return on assets. Although earnings are sustained by significant sales turnover, performance is affected by high levels of liquidity. Periods of unstable economic conditions, reflected by high inflation rates and the current financial crisis, have a strong negative impact on corporate performance.